Leo the Great and the spiritual rebuilding of a universal Rome - Wessel, Susan. (Vigiliae Christianae, Supplements, 2008)
Leo the Great was a major figure of the late Roman world whose life and work were profoundly intertwined with the political crisis of his day. As the western empire gradually succumbed to the advancing barbarian kingdoms, Leo understood that the papacy needed to expand its authority in order for the church to survive the demise of the political system. This book argues that his achievement was to transform the church not only in the practical level of administrative organization, but in the more fluid realm of thought and idea. The secular Rome that was crumbling was replaced with a Christian, universal Rome that he fashioned by infusing his theology with humanitarian ideals.